Analysis of expert’s opinion on requirements patterns for software product families framework using GQM method - Imam Ya'U, Badamasi; Nordin, Azlin; Salleh, Norsaremah (Springer, 2020)
Software product line engineering (SPLE), provides an opportunity to improve reuse of software artifacts through domain engineering and application engineering processes. During the domain engineering process, reuse activities of the product line are well-planned and subsequently executed in the application engineering process. This paper presents an analysis of interview result with experts in requirements engineering (RE) and software development for validating requirements pattern for software product families (RP-SPF) framework. The interview was conducted using goal questions metrics (GQM) method to define a goal and formulate research questions for conducting the interview. During the interview, 6 experts compared RP-SPF approach (systematic) with ad hoc (conventional) approach of reuse and documentation of requirements in terms of suitability, efficiency, and effectiveness in SPLE. The experts also gave their feedback on the perception of the use of RP-SPF tool. The analysis of the interview result shows that RP-SPF approach is suitable in SPLE and more efficient and effective than ad hoc approach of reuse and documentation of requirements.